A preliminary study to determine the incidence of gray mold (Botrytis cinerea) on tomato plants in greenhouses in several regions of Tartous Governorate (Latakia University Journal -Biological Sciences Series, 2023)
This study was conducted to determine the incidence of gray mold Botrytis cinerea in several tomato greenhouses during 2019-2020 seasons. The study included several regions of Tartous Governorate (Al Kharab, Al-Moqabariya, Banias, Bedaira, Hussain Al Bahr, Ssaya, Azzet, Matin Abou Rayya, and Wata Matin Al Sahel). The aim of this study was to find out the percentages of B.cinerea infestation on flowers, leaves, fruits, and the plant stems. Moreover, the impact of weather conditions and geographical area on the infection rate was considered and analyzed. The results showed that the plants grown in  Azzet region were the most susceptible to the infection with gray mold on all the studied parts of the plant in which the total infection ratio in this area hit 84.5% in February. While the lowest infection ratio was in Al-Moqabariya area on flowers, leaves, fruits and stems with a total ratio of 1.5% for the same month.